Scientific Examination of Art: Modern Techniques in Conservation and Analysis (The National Academies Press, 2005)
In March 2003, the National Academy of Sciences Arthur M. Sackler Colloquia presented the Scientific Examination of Art: Modern Techniques in Conservation and Analysis at the National Academy of Sciences Building in Washington, DC. Featuring senior investigators of specific methods and materials, the papers in this book examine the application of scientific methods to the study and conservation of art and cultural properties. The Arthur M. Sackler Colloquia of the National Academy of Sciences address scientific topics of broad and current interest, cutting across the boundaries of traditional disciplines and attracting up to 250 leading researchers in the field. These colloquia are made possible by a generous gift from Mrs. Jill Sackler, in memory of her husband, Arthur M. Sackler. For more information about the Sackler Colloquia, visit www.nasonline.org/sackler
Keywords: Engineering and Technology

Designing Nanostructures at the Interface between Biomedical and Physical Systems: Conference Focus Group Summaries (The National Academies Press, 2005)
Last November, the National Academies Keck Futures Initiative held the Designing Nanostructures at the Interface Between Biomedical and Physical Systems conference at which researchers from science, engineering and medicine discussed recent developments in nanotechnology, directions for future research, and possible biomedical applications. The centerpiece of the conference was breakout sessions in which ten focus groups of researchers from different fields spent eight hours developing research plans to solve various problems in the field of nanotechnology. Among the challenges were: Building a nanosystem that can isolate, sequence and identify RNA or DNA Developing a system to detect disease in vivo Sequencing a single molecule of protein Creating a biological system that will create a local hydrogen fuel source, and Growing a biological in vivo power source. Representatives from public and private funding organizations, government, industry, and the science media also participated in the focus groups. This book provides a summary of the conference focus groups. For more information about the conference, visit Keck Futures Initiative. The National Academies Keck Futures Initiative was launched in 2003 to stimulate new modes of scientific inquiry and break down the conceptual and institutional barriers to interdisciplinary research. The National Academies and the W.M. Keck Foundation believe considerable scientific progress and social benefit will be achieved by providing a counterbalance to the tendency to isolate research within academic fields. The Futures Initiative is designed to enable researchers from different disciplines to focus on new questions upon which they can base entirely new research, and to encourage better communication between scientists as well as between the scientific community and the public. Funded by a $40 million grant from the W.M. Keck Foundation, the National Academies Keck Futures Initiative is a 15-year effort to catalyze interdisciplinary inquiry and to enhance communication among researchers, funding agencies, universities, and the general public–with the object of stimulating interdisciplinary research at the most exciting frontiers. The Futures Initiative builds on three pillars of vital and sustained research: interdisciplinary encounters that counterbalance specialization and isolation; the identification and exploration of new research topics; and communication that bridges languages, cultures, habits of thought, and institutions. Toward these goals, the National Academies Keck Futures Initiative incorporates three core activities each year: Futures conferences, Futures grants, and National Academies Communication Awards.
Keywords: Health and Medicine; Engineering and Technology; Math, Chemistry, and Physics

Going to Extremes: Meeting the Emerging Demand for Durable Polymer Matrix Composites - National Research Council (The National Academies Press, 2005)
Advanced polymer matrix composites (PMC) have many advantages such as light weight and high specific strength that make them useful for many aerospace applications. Enormous uncertainty exists, however, in predicting long-term changes in properties of PMCs under extreme environmental conditions, which has limited their use. To help address this issue, the Department of Defense requested a study from the NRC to identify the barriers and limitations to the use of PMCs in extreme environments. The study was to focus on issues surrounding methodologies for predicting long-term performance. This report provides a review of the challenges facing application of PMCs in extreme environments, the current understanding of PMC properties and behavior, an analysis of the importance of data in developing effective models, and recommendations for improving long-term predictive methodologies.
Keywords: Engineering and Technology

Globalization of Materials R&D: Time for a National Strategy - National Research Council (The National Academies Press, 2005)
Materials Science and Engineering (MSE) R&D is spreading globally at an accelerating rate. As a result, the relative U.S. position in a number of MSE subfields is in a state of flux. To understand better this trend and its implications for the U.S. economy and national security, the Department of Defense (DOD) asked the NRC to assess the status and impacts of the global spread of MSE R&D. This report presents a discussion of drivers affecting U.S. companies' decisions about location of MSE R&D, an analysis of impacts on the U.S. economy and national security, and recommendations to ensure continued U.S. access to critical MSE R&D.
Keywords: Engineering and Technology

High-Performance Structural Fibers for Advanced Polymer Matrix Composites - National Research Council (The National Academies Press, 2005)
Military use of advanced polymer matrix composites (PMC)—consisting of a resin matrix reinforced by high-performance carbon or organic fibers—while extensive, accounts for less that 10 percent of the domestic market. Nevertheless, advanced composites are expected to play an even greater role in future military systems, and DOD will continue to require access to reliable sources of affordable, high-performance fibers including commercial materials and manufacturing processes. As a result of these forecasts, DOD requested the NRC to assess the challenges and opportunities associated with advanced PMCs with emphasis on high-performance fibers. This report provides an assessment of fiber technology and industries, a discussion of R&D opportunities for DOD, and recommendations about accelerating technology transition, reducing costs, and improving understanding of design methodology and promising technologies.
Keywords: Engineering and Technology

Key Performance Indicators for Federal Facilities Portfolios: Federal Facilities Council Technical Report Number 147 - National Research Council (The National Academies Press, 2005)
More than 30 federal departments and agencies with a wide range of missions and programs manage large inventories of facilities, also called portfolios. These portfolios range in size from a few hundred to more than a hundred thousand individual structures, buildings, and their supporting infrastructure. They are diverse in terms of facility types, mix of types, and geographic dispersal. For federal senior executives, facilities portfolio-related decisions revolve around the allocation of resources (staff, funding, time) for acquisition, renovation, operation, repair, and disposition of facilities. To make informed decisions, senior executives require information that will allow them to answer such questions as: What facilities do we have? What condition are they in? What facilities are needed to support the organization's missions? This study lays out a framework for developing and evaluating trends in facilities portfolio conditions, investments, and costs and identifies a set of key indicators that can be used to track performance over time. Some of the indicators are currently in use in some federal agencies; others will need to be developed.
Keywords: Engineering and Technology

An Assessment of the National Institute of Standards and Technology Measurement and Standards Laboratories: Fiscal Years 2004-2005 - National Research Council (The National Academies Press, 2005)
The National Institute of Standards and Technology (NIST) Measurements and Standards Laboratories (MSL) provide technical leadership for the nation’s measurement and standards infrastructure and assure the availability of essential reference data and measurement capabilities. At NIST’s request the National Research Council (NRC) carries out a biennial assessment of the seven MSL. The assessment focuses on each laboratory’s technical quality and merit; and effectiveness. It also examines the relevance of the NIST programs and how well laboratory facilities, equipment, and personnel are able to fulfill the MSL mission. This report presents an overall assessment of the MSL followed by detailed assessments of each of the seven laboratories.
Keywords: Engineering and Technology

Frontiers of Engineering: Reports on Leading-Edge Engineering from the 2004 NAE Symposium on Frontiers of Engineering - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 2005)
This volume includes 14 papers from the National Academy of Engineering's Tenth Annual U.S. Frontiers of Engineering Symposium held in September 2004. The U.S. Frontiers meeting brings together 100 outstanding engineers (ages 30-45) to learn from their peers and discuss leading-edge technologies in a range of fields. The 2004 symposium covered these four areas: engineering for extreme environments, designer materials, multiscale modeling, and engineering and entertainment. Papers in the book cover topics such as scalable mobile robots for deployment in polar climates, the challenges of landing on Mars, thin-film active materials, vascular tissue engineering, small-scale processes and large-scale simulations of the climate system, simulating physically accurate illumination in computer graphics, and designing socially intelligent robots, among others. Appendixes include information about the contributors, the symposium program, and a list of the meeting participants. The book is the tenth in a series covering the topics of the U.S. Frontiers of Engineering meetings.
Keywords: Engineering and Technology; Space and Aeronautics

Implications of Nanotechnology for Environmental Health Research - Institute of Medicine (The National Academies Press, 2005)
Nanotechnology is often described as an emerging technology - one that not only holds promise for society, but also is capable of revolutionizing our approaches to common problems. Nanotechnology is not a completely new field; however, it is only recently that discoveries in this field have advanced so far as to warrant examination of their impact upon the world around us. Nanotechnology has direct beneficial applications for medicine and the environment, but like all technologies it may have unintended effects that can adversely impact the environment, both within the human body and within the natural ecosystem. How does the science move forward in a way that best protects the public and gets health and safety right the first time? Implications of Nanotechnology for Environmental Health Research identifies the areas in which additional research is needed and the processes by which changes can occur.
Keywords: Engineering and Technology; Environment and Environmental Studies

Educating the Engineer of 2020: Adapting Engineering Education to the New Century - National Academy of Engineering (The National Academies Press, 2005)
Educating the Engineer of 2020 is grounded by the observations, questions, and conclusions presented in the best-selling book The Engineer of 2020: Visions of Engineering in the New Century. This new book offers recommendations on how to enrich and broaden engineering education so graduates are better prepared to work in a constantly changing global economy. It notes the importance of improving recruitment and retention of students and making the learning experience more meaningful to them. It also discusses the value of considering changes in engineering education in the broader context of enhancing the status of the engineering profession and improving the public understanding of engineering. Although certain basics of engineering will not change in the future, the explosion of knowledge, the global economy, and the way engineers work will reflect an ongoing evolution. If the United States is to maintain its economic leadership and be able to sustain its share of high-technology jobs, it must prepare for this wave of change.
Keywords: Education; Engineering and Technology

National Laboratories and Universities: Building New Ways to Work Together: Report of a Workshop - National Research Council (The National Academies Press, 2005)
This volume is a report of a workshop held in 2003 to address best practices and remaining challenges with respect to national laboratory-university collaborations.
Keywords: Education; Engineering and Technology

Building a Better Delivery System: A New Engineering/Health Care Partnership - National Academy of Engineering; Institute of Medicine (The National Academies Press, 2005)
In a joint effort between the National Academy of Engineering and the Institute of Medicine, this books attempts to bridge the knowledge/awareness divide separating health care professionals from their potential partners in systems engineering and related disciplines. The goal of this partnership is to transform the U.S. health care sector from an underperforming conglomerate of independent entities (individual practitioners, small group practices, clinics, hospitals, pharmacies, community health centers et. al.) into a high performance "system" in which every participating unit recognizes its dependence and influence on every other unit. By providing both a framework and action plan for a systems approach to health care delivery based on a partnership between engineers and health care professionals, Building a Better Delivery System describes opportunities and challenges to harness the power of systems-engineering tools, information technologies and complementary knowledge in social sciences, cognitive sciences and business/management to advance the U.S. health care system.
Keywords: Health and Medicine; Engineering and Technology

2003-2004 Assessment of the Army Research Laboratory - National Research Council (The National Academies Press, 2005)
Keywords: Conflict and Security Issues; Engineering and Technology

Interim Design Assessment for the Pueblo Chemical Agent Destruction Pilot Plant - National Research Council (The National Academies Press, 2005)
In 1996, Congress enacted directing the Department of Defense to assess and demonstrate technology alternatives to incineration for destruction of the chemical weapons stored at Pueblo Chemical and Blue Grass Army Depots. Since then, the National Research Council (NRC) has been carrying out evaluations of candidate technologies including reviews of engineering design studies and demonstration testing. Most recently, the NRC was asked by the Army to evaluate designs for pilot plants at Pueblo and Blue Grass. These pilot plants would use chemical neutralization for destroying the chemical agent and the energetics in the munitions stockpiles of these two depots. This report provides the interim assessment of the Pueblo Chemical Agent Destruction Pilot Plant (PCAPP) to permit adjustment of any significant problems as soon as possible. The report presents an analysis of the issues about the current PCAPP design and a series of findings and recommendations about ways to reduce concerns with involve the public more heavily in the process.
Keywords: Engineering and Technology; Environment and Environmental Studies

Implementing Health-Protective Features and Practices in Buildings: Workshop Proceedings: Federal Facilities Council Technical Report #148 - National Research Council (The National Academies Press, 2005)
Indoor environmental quality (IEQ) is influenced by building design; heating, ventilation, and air-conditioning systems; and construction materials, as well as by building operations, maintenance, and housekeeping procedures. Increasing evidence suggests that adverse health outcomes in employees, students, hospital patients, and others are linked to the presence of indoor pollutants and other aspects of poor-quality indoor environments. Implementing Health-Protective Features and Practices in Buildings explores this issue and discusses ongoing research and possible strategies for implementing changes in standards and practices for indoor environmental quality.
Keywords: Engineering and Technology; Health and Medicine

Nanotechnology for the Intelligence Community (The National Academies Press, 2005)
The emergence of nanotechnology as a major science and technology research topic has sparked substantial interest by the intelligence community. In particular the community is interested both in the potential for nanotechnology to assist intelligence operations and threats it could create. To explore these questions, the Intelligence Technology Innovation Center asked the National Research Council to conduct a number of activities to illustrate the potential for nanotechnology to address key intelligence community needs. In 2004, workshop reports were issued on power systems and on positioning and sensing technologies. The final report provides an assessment of a wide range of additional technologies. The report also presents a series of findings and recommendations about areas of opportunities for the intelligence community and strategies for exploiting these opportunities.
Keywords: Conflict and Security Issues

Review of the Biomedical Proposals to the 2005 Wright Centers of Innovation and the Biomedical Research and Technology Transfer Partnership Award Program of the State of Ohio: Letter Report - National Research Council (The National Academies Press, 2005)
Keywords: Engineering and Technology; Health and Medicine

Linkages: Manufacturing Trends in Electronic Interconnection Technology - National Research Council (The National Academies Press, 2005)
Over the past two decades, the Department of Defense has been moving toward commercial-military integration for manufacturing, while at the same time, the printed circuit board industry has been moving steadily offshore. Today, many in DoD, the U.S. Congress, and the federal government lack a clear understanding of the importance of high-quality, trustworthy printed circuit boards (PrCBs) for properly functioning weapons and other defense systems and components. To help develop this understanding, DOD requested the NRC to identify and assess the key issues affecting PrCBs for military use. This report presents a discussion of how to ensure DOD's access to reliable printed circuits; an assessment of its vulnerability to the global printed circuit supply chain; and suggestions about ways to secure the design and manufacture of printed circuits. In addition, this report offers recommendations to help DoD (1) preserve existing systems' capabilities, (2) improve the military's access to currently available PrCBs, and (3) ensure access to future PrCB technology. The recommendations reflect the need to achieve these goals at reasonable cost and in concert with evolving environmental regulations.
Keywords: Engineering and Technology; Conflict and Security Issues

Technological Options for User-Authorized Handguns: A Technology-Readiness Assessment - National Academy of Engineering (The National Academies Press, 2005)
Misuse of handguns is a significant factor in deaths, morbidity, and crime in the United States. One approach to reducing certain types of handgun misuse is to create a user-authorized handgun (UAHG), a firearm that can be operated only by an authorized user(s). Technological Options for User-Authorized Handguns clarifies the technical challenges of developing a reliable UAHG. This report determines the requirements and specifications of UAHGs for those concerned with public and/or personal safety, and identifies technologies that could satisfy these needs.
Keywords: Engineering and Technology; Conflict and Security Issues

Enhancing the Community College Pathway to Engineering Careers - National Academy of Engineering; National Research Council (The National Academies Press, 2005)
Community colleges play an important role in starting students on the road to engineering careers, but students often face obstacles in transferring to four-year educational institutions to continue their education. Enhancing the Community College Pathway to Engineering Careers, a new book from the National Academy of Engineering and the National Research Council, discusses ways to improve the transfer experience for students at community colleges and offers strategies to enhance partnerships between those colleges and four-year engineering schools to help students transfer more smoothly. In particular, the book focuses on challenges and opportunities for improving transfer between community colleges and four-year educational institutions, recruitment and retention of students interested in engineering, the curricular content and quality of engineering programs, opportunities for community colleges to increase diversity in the engineering workforce, and a review of sources of information on community college and transfer students. It includes a number of current policies, practices, and programs involving community college–four-year institution partnerships.
Keywords: Education; Engineering and Technology